Crack growth performance of tyre compounds - Sumner A J; Eisele U G; Kelbch S A (Rubber World, 1995)
The resistance of the various tyre compounds to crack growth is one of the most crucial requirements of a tyre, especially with respect to safety. This article describes a new machine called the tear analyser which, when operated under particular conditions, has been found to be capable of predicting, in the laboratory, the same crack growth resistance of various rubber parts of the tyre as found in tyre machine tests. Components of the tyre that have been investigated include sidewall, cushion gum, breaker, bias ply truck tread, radial ply truck tread and inner linear compounds. An experimental NR/EPDM compound formulation was tested against a stndard NR/BR sidewall compound.
Keywords: Crack growth; EPDM; Tyre compounds